Oil-resistant flame-retardant composite sealing material and preparation method and application thereof

By using a combination and crosslinking technology of a variety of polymer materials in the sealing material, combining specific fillers and flame retardants, the checks and balances between oil resistance and flame retardant properties and mechanical properties are solved, and the comprehensive performance of the sealing material is achieved Improve and extend service life.

CN119119654AInactive Publication Date: 2024-12-13CHANGCHUN LANTIAN SEAL IND CO LTD

Patent Information

Application Number
CN202411620556.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When existing oil-resistant and flame-retardant sealing materials improve oil-resistant and flame-retardant sealing materials often lead to degradation of mechanical properties, making it difficult to improve the overall performance, and there are checks and balances between different properties.

Method used

Use fluoro-rubber, nitrile rubber, ethylene propylene ternary rubber, chlorinated polyethylene and maleic anhydride grafted polypropylene in a certain proportion, and add hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethyl Basic siloxane silsesquioxane cross-linked polymer, E-GMA-VA terpolymer, magnesium hydroxide, basalt fiber powder, triphenyl phosphate, expandable graphite and other components, optimized by vulcanization treatment and molding process , prepare composite sealing materials with good mechanical properties, oil resistance and flame retardant properties.

Benefits of technology

It significantly improves the oil resistance, flame retardant performance and service life of the sealing material, ensures the stability and safety of the material in high temperature, high pressure and chemical media environments, and extends the service life of the sealing material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to an oil-resistant flame-retardant composite sealing material as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. Fluororubber, nitrile rubber, ethylene propylene diene monomer, chlorinated polyethylene and maleic anhydride grafted polypropylene are adopted to prepare composite rubber according to a certain proportion; then adding hydrogenated polyisobutene, a vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, an E-GMA-VA terpolymer, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate, triphenyl phosphate, expansible graphite, zinc borate, a vulcanizing agent, an accelerant, an anti-aging agent, a plasticizer and other components according to a proportion, and performing banburying in special steps; the prepared sealing material has good mechanical properties, especially has oil resistance and flame retardance, and the service life is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an oil-resistant and flame-retardant composite sealing material and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry, the operating environment of various mechanical equipment is becoming increasingly complex. In many industrial fields, such as petrochemicals, automobile manufacturing, aerospace, etc., equipment often needs to work in an environment of high temperature, high pressure and contact with various chemicals. Among them, oil substances are one of the common working media. In these environments, ordinary sealing materials are easily corroded by oil, resulting in reduced sealing performance or even failure. For example, in the petrochemical industry, equipment such as pipelines, valves, and pumps require sealing materials that can resist the erosion of various petroleum products while ensuring the safe operation of the equipment. If the sealing material is not oil-resistant, oil substances may penetrate through the sealing part and cause leakage, which will not only waste resources, but also cause serious safety accidents such as fire and explosion; in addition, if the sealing material does not have flame retardant properties, it is easy to burn and aggravate the spread of fire. For example, in electrical equipment, the sealing material needs to be able to prevent the spread of flames to protect the electronic components and circuits inside the equipment. In the aerospace field, the sealing materials of aircraft and spacecraft must have excellent flame retardant properties to ensure safety in emergency situations.

[0003] The continuous progress of materials science and engineering technology has provided strong support for the research and development of oil-resistant and flame-retardant sealing materials. In recent years, the development of new polymer materials, composite materials and nanotechnology has provided new ways to develop sealing materials with excellent performance. For example, by adding special oil-resistant agents and flame retardants to polymer materials, the oil resistance and flame retardancy of the materials can be significantly improved.

[0004] However, there are still some problems with oil-resistant and flame-retardant sealing materials: (1) Oil resistance and flame retardancy are mutually restrained: When the oil resistance of some materials is improved, their flame retardancy will be affected; conversely, the treatment to enhance the flame retardancy will reduce the oil resistance of the material. For example, nitrile rubber is a commonly used sealing material with good oil resistance. However, when some inorganic flame retardants (such as aluminum hydroxide and other flame retardants) are added to improve its flame retardancy, although the flame retardancy can be improved, it will make the nitrile rubber more prone to swelling or aging when it comes into contact with oil substances, thereby reducing its oil resistance.

[0005] (2) The contradiction between mechanical properties and oil resistance and flame retardancy: In order to achieve good oil resistance and flame retardancy, it is often necessary to add a large amount of fillers, flame retardants and other additives, which will lead to a decrease in the mechanical properties of the material, such as tensile strength, tear strength, elastic modulus, etc., affecting the service life and sealing effect of the sealing material.

[0006] The performance of the above components is mutually restrained, which makes it difficult to achieve comprehensive improvement in the performance of the sealing material. Therefore, it is necessary to continuously improve the comprehensive performance of the sealing material from aspects such as material selection, ratio design, and preparation process design to achieve safer, more reliable, and longer life requirements. Summary of the invention

[0007] The existing sealing materials have performances that are mutually counterbalanced, and it is difficult to achieve comprehensive improvement in oil resistance, flame retardancy, and mechanical properties. The present invention provides an oil-resistant and flame-retardant composite sealing material and a preparation method thereof. The composite rubber is prepared by using fluororubber, nitrile rubber, EPDM rubber, chlorinated polyethylene, and maleic anhydride grafted polypropylene in a certain proportion, and then hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, E-GMA-VA terpolymer, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate, triphenyl phosphate, expandable graphite, zinc borate, vulcanizer, accelerator, antioxidant, plasticizer and other ingredients are added in proportion for mixing, and the prepared sealing material has good mechanical properties, especially oil resistance and flame retardancy, and the service life is greatly extended. The specific technical scheme is as follows: An oil-resistant and flame-retardant composite sealing material comprises the following raw materials in parts by mass: 72 to 98 parts of composite modified rubber, 5 to 10 parts of polytetrafluoroethylene powder, 0.5 to 1.5 parts of hydrogenated polyisobutylene, 1 to 3 parts of vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer, 1 to 3 parts of E-GMA-VA terpolymer, 8 to 12 parts of magnesium hydroxide, 5 to 10 parts of basalt fiber powder, 1 to 3 parts of ammonium polyphosphate, 1 to 3 parts of triphenyl phosphate, 0.5 to 0.8 parts of expandable graphite, 2 to 5 parts of zinc borate, 1.5 to 3 parts of vulcanizer, 0.5 to 1.5 parts of accelerator, 1 to 2 parts of antioxidant, and 5 to 8 parts of plasticizer.

[0008] In the above-mentioned sealing material, the preparation method of the composite modified rubber comprises the following steps: according to the mass ratio, fluororubber:nitrile rubber:ethylene propylene diene rubber:chlorinated polyethylene:maleic anhydride grafted polypropylene = (50-60): (15-20): (5-10): (1-5): (1-3), fluororubber, ethylene propylene diene rubber and chlorinated polyethylene are banburying at 130°C to 150°C for 10min to 15min to obtain a banburying material A; nitrile rubber and maleic anhydride grafted polypropylene are banburying at 110°C to 130°C for 5min to 10min to obtain a banburying material B; banburying materials A and banburying materials B are mixed and banburying at 110°C to 130°C for 10min to 15min to obtain a composite modified rubber.

[0009] In the above sealing material, the particle size of the polytetrafluoroethylene powder is less than 20 μm.

[0010] In the above sealing material, the particle size of the magnesium hydroxide is less than 5 μm.

[0011] In the above sealing material, the particle size of the basalt fiber powder is less than 15 μm.

[0012] In the above sealing material, the particle size of the ammonium polyphosphate is less than 10 μm.

[0013] In the above sealing material, the particle size of the zinc borate is less than 5 μm.

[0014] In the above sealing material, the vulcanizing agent includes bisphenol AF and phenyl-phenyl-diisopropylbenzene peroxide (DCP-S), and the mass ratio is bisphenol AF:phenyl-diisopropylbenzene peroxide (DCP-S) = (5-6): (2-3).

[0015] In the above sealing material, the accelerator includes accelerator M (2-mercaptobenzothiazole) and accelerator TMTD (tetramethylthiuram disulfide), and the mass ratio is accelerator M (2-mercaptobenzothiazole): accelerator TMTD (tetramethylthiuram disulfide) = (5-6): (2-3).

[0016] In the above sealing material, the antioxidant is antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer) or antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine).

[0017] In the above sealing material, the plasticizer is dioctyl phthalate.

[0018] The method for preparing the above-mentioned oil-resistant flame-retardant composite sealing material comprises the following steps: S1: premix polytetrafluoroethylene powder, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate and zinc borate uniformly according to weight proportions to obtain a mixture A; S2: Add the composite modified rubber into an internal mixer according to the mass fraction, and mix at 40℃~60℃ for 3min~5min; then add hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer, and E-GMA-VA terpolymer, and mix at 80℃~100℃ for 3min~5min; then add mixture A, and mix at 100℃~120℃ for 10min~15min; then add triphenyl phosphate and expandable graphite, and mix at 130℃~150℃ for 10min~15min; then cool to 80℃~90℃, add vulcanizer, accelerator, antioxidant and plasticizer, and mix at 80℃~90℃ for 10min~15min to obtain a mixed material; S3: Extruding or compression molding the mixed material to obtain a molding material; S4: placing the molding material into a vulcanization device for vulcanization treatment to obtain a sealing material.

[0019] In S3 of the above preparation method, the temperature of the extrusion molding is controlled at 60°C to 80°C, the temperature of the compression molding is controlled at 140°C to 160°C, and the pressure of the compression molding is controlled at 15MPa to 25MPa.

[0020] In S4 of the above preparation method, the parameters of the vulcanization treatment are: primary vulcanization, temperature 150°C ~ 160°C, time 5min ~ 10min, pressure 10MPa ~ 15MPa; secondary vulcanization, temperature 160°C ~ 180°C, time 15min ~ 20min, pressure 15MPa ~ 20MPa; tertiary vulcanization, temperature 180°C ~ 220°C, time 15min ~ 20min, pressure 15MPa ~ 20MPa.

[0021] The above-mentioned oil-resistant and flame-retardant composite sealing material is used to prepare sealing pads or sealing rings, and the minimum use thickness is 1.5 mm.

[0022] The oil-resistant flame-retardant composite sealing material and the preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art: 1. The present invention mixes and kneads fluororubber, nitrile rubber, EPDM rubber, chlorinated polyethylene, and maleic anhydride grafted polypropylene in a certain proportion, first kneads fluororubber, EPDM rubber, and chlorinated polyethylene to obtain a kneaded material A; kneads nitrile rubber and maleic anhydride grafted polypropylene to obtain a kneaded material B; and kneads the kneaded materials A and B to obtain a composite modified rubber. The two-step kneading can be used to treat the rubber combination with different characteristics in a more targeted manner, so that the combination between different rubbers is more sufficient and uniform. The adverse interaction between different rubbers in the initial kneading is avoided, thereby improving the bonding degree. The reaction process is optimized, so that the maleic anhydride grafted polypropylene can play a better role in kneading with nitrile rubber, and promote the combination between different kneaded materials. Multiple rubbers are compounded, and the molecular structures and characteristics of different rubbers complement each other, thereby improving the tolerance to different types of oils. Nitrile rubber has good oil resistance, fluororubber has certain flame retardancy, and chlorinated polyethylene also plays a positive role in flame retardancy. The synergistic effect of multiple components makes the composite rubber perform better in oil resistance and flame retardancy.

[0023] 2. Design of vulcanizing agents according to the characteristics of composite modified rubber includes bisphenol AF and phenyl-phenyl-diisopropylbenzene peroxide (DCP-S), with a mass ratio of bisphenol AF: phenyl-diisopropylbenzene peroxide (DCP-S) = (5-6): (2-3). The two vulcanizing agents are used in a certain ratio to achieve more uniform and sufficient vulcanization, so that the composite modified rubber performs better in terms of physical properties and chemical stability. It is improved in terms of mechanical properties, heat resistance, aging resistance, etc., while taking into account different performance requirements. Bisphenol AF and DCP-S have different vulcanization mechanisms and characteristics. Bisphenol AF reacts chemically with rubber molecules to form a cross-linked structure. DCP-S initiates the cross-linking of rubber molecules through free radical reactions. When the two are used together, they play a synergistic role to improve the vulcanization efficiency and cross-linking density. Different vulcanizing agents play a role at different stages or for different rubber components, thereby achieving more comprehensive and more effective vulcanization. Since the composite modified rubber contains a variety of different rubber components, a single vulcanizing agent cannot meet the vulcanization requirements of all components. The combination of the two vulcanizing agents can better adapt to the characteristics of different rubbers and ensure that each component can be fully vulcanized. For example, for different rubbers such as fluororubber, nitrile rubber, EPDM rubber, etc., bisphenol AF and DCP-S can react with them to different degrees, respectively, to improve the pertinence and effect of vulcanization. Bisphenol AF helps to improve the heat resistance and aging resistance of vulcanized rubber, while DCP-S has advantages in mechanical properties and cross-linking speed. The combination of the two can give full play to their respective advantages and enable the composite modified rubber to obtain better performance.

[0024] 3. Vulcanization accelerators include accelerator M (2-mercaptobenzothiazole) and accelerator TMTD (tetramethylthiuram disulfide), with a mass ratio of accelerator M (2-mercaptobenzothiazole): accelerator TMTD (tetramethylthiuram disulfide) = (5-6): (2-3). The two accelerators are used in a certain proportion to accelerate the vulcanization reaction, shorten the vulcanization time, and improve production efficiency; make the rubber vulcanization more uniform in the entire system, reduce the local under-vulcanization or over-vulcanization, thereby improving the quality stability of rubber products; enhance the tensile strength, tear strength, wear resistance and other mechanical properties of the composite modified rubber. Through reasonable accelerator matching, the heat resistance and aging resistance of rubber can be improved to a certain extent, and the service life of rubber products can be extended.

[0025] Among them, accelerator M (2-mercaptobenzothiazole) and accelerator TMTD (tetramethylthiuram disulfide) have different promotion mechanisms. Accelerator M mainly reacts with vulcanizing agents such as sulfur or peroxide to generate active sulfur or free radicals, thereby initiating the cross-linking reaction of rubber molecules. Accelerator TMTD is a super accelerator that can quickly promote the vulcanization reaction. When the two are used together, they can play a synergistic role in promoting the speed and efficiency of the vulcanization reaction. Different accelerators play a role at different stages or for different rubber components, thereby achieving more comprehensive and effective promotion of vulcanization. The combination of accelerator M and accelerator TMTD can adjust the shape of the vulcanization curve to make it more in line with the actual production needs. For composite modified rubber, due to its complex composition, it is necessary to achieve precise control of the vulcanization process through reasonable accelerator matching. The combined action of accelerator M and accelerator TMTD can increase the cross-linking density of the composite modified rubber, make the rubber molecules more tightly bonded, and thus improve the mechanical properties and heat resistance of the rubber.

[0026] 4. Polytetrafluoroethylene powder, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate and zinc borate are added to the material. Polytetrafluoroethylene has an extremely low friction coefficient and excellent chemical stability. Its powder is evenly dispersed in the rubber, forming a low-friction protective film on the sealing surface, reducing wear and friction heat, improving wear resistance and self-lubrication, and enhancing the chemical corrosion resistance of the sealing material. Magnesium hydroxide, as a flame retardant, plays a role in flame retardancy and smoke suppression; at the same time, it can absorb certain acidic substances and improve the stability of the sealing material. Basalt fiber has high strength, high modulus and good heat resistance. The fiber powder is evenly dispersed in the rubber, which can form a three-dimensional reinforced network, effectively transfer stress, and improve the overall strength and stiffness of the sealing material. The heat resistance of basalt fiber enables the sealing material to maintain good performance in a high temperature environment. Ammonium polyphosphate is a flame retardant, which promotes carbonization, forms a heat-insulating and oxygen-isolating carbon layer, and prevents the spread of combustion. Zinc borate is used for flame retardancy and smoke suppression, and cooperates with other flame retardants to improve the flame retardant effect; at the same time, it has a certain anti-corrosion effect.

[0027] The chemical corrosion resistance of polytetrafluoroethylene powder improves the sealing material's tolerance to chemical media such as oils to a certain extent. The presence of basalt fiber powder and other ingredients can make the structure of the sealing material more compact and reduce the penetration of oil substances. Magnesium hydroxide, ammonium polyphosphate and zinc borate, as flame retardants, work synergistically through different mechanisms to improve the flame retardant properties of the sealing material.

[0028] 5. During the mixing process of the sealing material, hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, and E-GMA-VA terpolymer are also added. Hydrogenated polyisobutylene improves the flexibility, low temperature resistance, and aging resistance of the sealing material; hydrogenated polyisobutylene has good elasticity and low temperature performance, its molecular structure is stable, not easily oxidized, and can maintain good flexibility at low temperatures, while improving the aging resistance of the sealing material. Vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer enhances the heat resistance, weather resistance, and chemical corrosion resistance of the sealing material. The polymer has excellent thermal stability, weather resistance, and chemical inertness, and can maintain good performance under high temperature and harsh environments, while improving the chemical corrosion resistance of the sealing material. E-GMA-VA terpolymer improves the adhesion, compatibility and processing performance of sealing materials, thereby improving the oil resistance and flame retardancy of sealing materials; E-GMA-VA terpolymer has good adhesion and compatibility, and can be well combined with composite modified rubber and other additives to improve the overall performance of sealing materials; at the same time, it can also improve the processing performance of sealing materials, making them easier to extrude and vulcanize. These three substances work together to comprehensively improve the various properties of sealing materials, making them significantly improved in terms of flexibility, low temperature resistance, heat resistance, weather resistance, chemical corrosion resistance, adhesion and processing performance.

[0029] Hydrogenated polyisobutylene has good chemical stability and low polarity, and can resist the erosion of oil substances. It can fill the gaps between rubber molecules in the sealing material, making the structure more compact and reducing the penetration channel of oil. Vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosspolymer has excellent chemical corrosion resistance and good tolerance to oil substances. Its cross-linked structure can enhance the integrity of the sealing material and prevent the diffusion of oil substances. The good compatibility of E-GMA-VA terpolymer can better combine the components and improve the oil resistance of the sealing material. At the same time, it can reduce the impact of oil on the sealing material through interaction with oil substances. Hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosspolymer and E-GMA-VA terpolymer work together to form a dense protective layer on the surface of the sealing material to reduce the penetration of oil substances. At the same time, they cooperate with the composite modified rubber to enhance the overall oil resistance of the sealing material.

[0030] 6. During the mixing process of the sealing material, triphenyl phosphate and expandable graphite are also added. As a flame retardant, triphenyl phosphate plays a role in flame retardancy and smoke suppression; during the combustion process, triphenyl phosphate decomposes to produce phosphoric acid and other substances, which promotes the formation of a carbon layer on the surface of the sealing material, plays a role in heat insulation and oxygen isolation, and prevents the continuation of combustion; at the same time, it can also suppress the generation of smoke. It expands at high temperatures to form a worm-like structure, which plays a role in heat insulation and oxygen isolation; expandable graphite expands rapidly when heated to form a worm-like expanded graphite layer. This structure can effectively prevent the transfer of heat and oxygen, thereby playing a flame retardant role.

[0031] Triphenyl phosphate mainly promotes the formation of carbon layer through the substances produced by decomposition, while expandable graphite forms a worm-like structure to insulate heat and oxygen. The synergistic effect of the two can prevent the occurrence and spread of combustion at different stages and in different ways, thereby improving the flame retardant effect of the sealing material. At the same time, the expansion of expandable graphite can also make up for the shortcomings of triphenyl phosphate in heat insulation, further enhancing the flame retardant properties of the sealing material.

[0032] 7. Hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer and E-GMA-VA terpolymer can provide a better dispersion environment for triphenyl phosphate and expandable graphite while being oil resistant, making them more effective in playing a flame retardant role. These substances work together to form a comprehensive protection system to improve the oil resistance and flame retardant performance of the sealing material.

[0033] 8. The present invention designs the mixing steps and parameters according to the combination characteristics of each component of the sealing material, and designs the parameters of the vulcanization treatment, so as to ensure that the sealing material achieves high performance and has good practicality. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0035] Example 1: An oil-resistant and flame-retardant composite sealing material, the sealing material comprising the following raw materials in parts by mass: 75 parts of composite modified rubber, 7.5 parts of polytetrafluoroethylene powder, 1 part of hydrogenated polyisobutylene, 2 parts of vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, 2 parts of E-GMA-VA terpolymer, 10 parts of magnesium hydroxide, 8 parts of basalt fiber powder, 2 parts of ammonium polyphosphate, 2 parts of triphenyl phosphate, 0.7 parts of expandable graphite, 3 parts of zinc borate, 2.2 parts of vulcanizer, 1 part of accelerator, 1.5 parts of antioxidant and 6.5 parts of plasticizer.

[0036] The preparation method of the composite modified rubber includes the following steps: according to the mass ratio of fluororubber:nitrile rubber:ethylene propylene diene rubber:chlorinated polyethylene:maleic anhydride grafted polypropylene = 55:18:8:3:2, the fluororubber, ethylene propylene diene rubber and chlorinated polyethylene are banburying at 140°C for 12 minutes to obtain a banburying material A; the nitrile rubber and maleic anhydride grafted polypropylene are banburying at 120°C for 8 minutes to obtain a banburying material B; the banburying materials A and B are mixed and banburying at 120°C for 12 minutes to obtain a composite modified rubber.

[0037] Among them, the particle size of polytetrafluoroethylene powder is less than 20 μm. The particle size of magnesium hydroxide is less than 5 μm. The particle size of basalt fiber powder is less than 15 μm. The particle size of ammonium polyphosphate is less than 10 μm. The particle size of zinc borate is less than 5 μm.

[0038] The vulcanizing agent includes bisphenol AF and phenyl-phenyl-diisopropylbenzene peroxide (DCP-S), and the mass ratio is bisphenol AF:phenyl-diisopropylbenzene peroxide (DCP-S) = 5.5:2.5.

[0039] The accelerator includes accelerator M (2-mercaptobenzothiazole) and accelerator TMTD (tetramethylthiuram disulfide), and the mass ratio is accelerator M (2-mercaptobenzothiazole): accelerator TMTD (tetramethylthiuram disulfide) = 5.5:2.5.

[0040] The antioxidant is antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer) or antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine).

[0041] Wherein, the plasticizer is dioctyl phthalate.

[0042] The method for preparing the above-mentioned oil-resistant flame-retardant composite sealing material comprises the following steps: S1: premix polytetrafluoroethylene powder, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate and zinc borate uniformly according to weight proportions to obtain a mixture A; S2: Add the composite modified rubber into an internal mixer according to the mass fraction, and mix at 50°C for 4 minutes; then add hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, and E-GMA-VA terpolymer, and mix at 90°C for 4 minutes; then add mixture A, and mix at 110°C for 12 minutes; then add triphenyl phosphate and expandable graphite, and mix at 140°C for 12 minutes; then cool to 85°C, add vulcanizer, accelerator, antioxidant and plasticizer, and mix at 85°C for 12 minutes to obtain a mixed material; S3: Extruding the mixed material, and controlling the extrusion molding temperature at 80° C. to obtain a molding material; S4: Put the molding material into the vulcanization equipment for vulcanization treatment. The vulcanization treatment parameters are: primary vulcanization, temperature 155°C, time 8min, pressure 12MPa; secondary vulcanization, temperature 170°C, time 18min, pressure 18MPa; tertiary vulcanization, temperature 200°C, time 18min, pressure 18MPa; cooling, trimming, and obtaining the sealing material.

[0043] The oil-resistant and flame-retardant composite sealing material of this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.5 mm.

[0044] Example 2: An oil-resistant and flame-retardant composite sealing material, the sealing material comprising the following raw materials in parts by mass: 72 parts of composite modified rubber, 5 parts of polytetrafluoroethylene powder, 0.5 parts of hydrogenated polyisobutylene, 1 part of vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, 1 part of E-GMA-VA terpolymer, 8 parts of magnesium hydroxide, 5 parts of basalt fiber powder, 1 part of ammonium polyphosphate, 1 part of triphenyl phosphate, 0.5 parts of expandable graphite, 2 parts of zinc borate, 1.5 parts of vulcanizer, 0.5 parts of accelerator, 1 part of antioxidant and 5 parts of plasticizer.

[0045] The preparation method of the composite modified rubber includes the following steps: according to the mass ratio of fluororubber:nitrile rubber:ethylene propylene diene rubber:chlorinated polyethylene:maleic anhydride grafted polypropylene = 50:15:5:1:1, the fluororubber, ethylene propylene diene rubber and chlorinated polyethylene are banburying at 130°C for 10 minutes to obtain a banburying material A; the nitrile rubber and maleic anhydride grafted polypropylene are banburying at 110°C for 5 minutes to obtain a banburying material B; the banburying materials A and B are mixed and banburying at 110°C for 10 minutes to obtain a composite modified rubber.

[0046] Among them, the particle size of polytetrafluoroethylene powder is less than 20 μm. The particle size of magnesium hydroxide is less than 5 μm. The particle size of basalt fiber powder is less than 15 μm. The particle size of ammonium polyphosphate is less than 10 μm. The particle size of zinc borate is less than 5 μm.

[0047] The vulcanizing agent includes bisphenol AF and phenyl-phenyl-diisopropylbenzene peroxide (DCP-S), and the mass ratio is bisphenol AF:phenyl-diisopropylbenzene peroxide (DCP-S) = 5:2.

[0048] The accelerator includes accelerator M (2-mercaptobenzothiazole) and accelerator TMTD (tetramethylthiuram disulfide), and the mass ratio is accelerator M (2-mercaptobenzothiazole): accelerator TMTD (tetramethylthiuram disulfide) = 5:2.

[0049] The antioxidant is antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer) or antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine).

[0050] Wherein, the plasticizer is dioctyl phthalate.

[0051] The method for preparing the above-mentioned oil-resistant flame-retardant composite sealing material comprises the following steps: S1: premix polytetrafluoroethylene powder, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate and zinc borate uniformly according to weight proportions to obtain a mixture A; S2: Add the composite modified rubber into an internal mixer according to the mass fraction, and mix at 40°C for 3 minutes; then add hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, and E-GMA-VA terpolymer, and mix at 80°C for 3 minutes; then add mixture A, and mix at 100°C for 10 minutes; then add triphenyl phosphate and expandable graphite, and mix at 130°C for 10 minutes; then cool to 80°C, add vulcanizer, accelerator, antioxidant and plasticizer, and mix at 80°C for 10 minutes to obtain a mixed material; S3: Extruding the mixed material, and controlling the extrusion molding temperature at 70° C. to obtain a molding material; S4: Put the molding material into the vulcanization equipment for vulcanization treatment. The vulcanization treatment parameters are: primary vulcanization, temperature 150°C, time 5min, pressure 10MPa; secondary vulcanization, temperature 160°C, time 15min, pressure 15MPa; tertiary vulcanization, temperature 180°C, time 15min, pressure 15MPa; cooling, trimming, and obtaining the sealing material.

[0052] The oil-resistant and flame-retardant composite sealing material of this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.5 mm.

[0053] Example 3: An oil-resistant and flame-retardant composite sealing material, the sealing material comprising the following raw materials in parts by mass: 72 parts of composite modified rubber, 10 parts of polytetrafluoroethylene powder, 0.5 parts of hydrogenated polyisobutylene, 3 parts of vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, 1 part of E-GMA-VA terpolymer, 12 parts of magnesium hydroxide, 5 parts of basalt fiber powder, 3 parts of ammonium polyphosphate, 1 part of triphenyl phosphate, 0.8 parts of expandable graphite, 2 parts of zinc borate, 3 parts of vulcanizer, 0.5 parts of accelerator, 2 parts of antioxidant and 5 parts of plasticizer.

[0054] The preparation method of the composite modified rubber includes the following steps: according to the mass ratio of fluororubber:nitrile rubber:ethylene propylene diene rubber:chlorinated polyethylene:maleic anhydride grafted polypropylene = 60:15:10:1:3, the fluororubber, ethylene propylene diene rubber and chlorinated polyethylene are banburying at 130°C for 15 minutes to obtain a banburying material A; the nitrile rubber and maleic anhydride grafted polypropylene are banburying at 110°C for 10 minutes to obtain a banburying material B; the banburying materials A and B are mixed and banburying at 110°C for 15 minutes to obtain a composite modified rubber.

[0055] Among them, the particle size of polytetrafluoroethylene powder is less than 20 μm. The particle size of magnesium hydroxide is less than 5 μm. The particle size of basalt fiber powder is less than 15 μm. The particle size of ammonium polyphosphate is less than 10 μm. The particle size of zinc borate is less than 5 μm.

[0056] The vulcanizing agent includes bisphenol AF and phenyl-phenyl-diisopropylbenzene peroxide (DCP-S), and the mass ratio is bisphenol AF:phenyl-diisopropylbenzene peroxide (DCP-S) = 5:3.

[0057] The accelerator includes accelerator M (2-mercaptobenzothiazole) and accelerator TMTD (tetramethylthiuram disulfide), and the mass ratio is accelerator M (2-mercaptobenzothiazole): accelerator TMTD (tetramethylthiuram disulfide) = 5:3.

[0058] The antioxidant is antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer) or antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine).

[0059] Wherein, the plasticizer is dioctyl phthalate.

[0060] The method for preparing the above-mentioned oil-resistant flame-retardant composite sealing material comprises the following steps: S1: premix polytetrafluoroethylene powder, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate and zinc borate uniformly according to weight proportions to obtain a mixture A; S2: Add the composite modified rubber into an internal mixer according to the mass fraction, and mix at 40°C for 5 minutes; then add hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer, and E-GMA-VA terpolymer, and mix at 80°C for 5 minutes; then add mixture A, and mix at 100°C for 15 minutes; then add triphenyl phosphate and expandable graphite, and mix at 130°C for 15 minutes; then cool to 80°C, add vulcanizer, accelerator, antioxidant and plasticizer, and mix at 90°C for 10 minutes to obtain a mixed material; S3: Extruding the mixed material, and controlling the extrusion molding temperature at 60° C. to obtain a molding material; S4: Put the molding material into the vulcanization equipment for vulcanization treatment. The vulcanization treatment parameters are: primary vulcanization, temperature 160°C, time 5min, pressure 15MPa; secondary vulcanization, temperature 160°C, time 20min, pressure 15MPa; tertiary vulcanization, temperature 220°C, time 15min, pressure 20MPa; cooling, trimming, and obtaining the sealing material.

[0061] The oil-resistant and flame-retardant composite sealing material of this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.5 mm.

[0062] Example 4: An oil-resistant and flame-retardant composite sealing material, the sealing material comprising the following raw materials in parts by mass: 98 parts of composite modified rubber, 10 parts of polytetrafluoroethylene powder, 1.5 parts of hydrogenated polyisobutylene, 3 parts of vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, 3 parts of E-GMA-VA terpolymer, 12 parts of magnesium hydroxide, 10 parts of basalt fiber powder, 3 parts of ammonium polyphosphate, 3 parts of triphenyl phosphate, 0.8 parts of expandable graphite, 5 parts of zinc borate, 3 parts of vulcanizer, 1.5 parts of accelerator, 2 parts of antioxidant and 8 parts of plasticizer.

[0063] The preparation method of the composite modified rubber comprises the following steps: in a mass ratio of fluororubber:nitrile rubber:ethylene propylene diene rubber:chlorinated polyethylene:maleic anhydride grafted polypropylene = 60:20:10:5:3, the fluororubber, ethylene propylene diene rubber and chlorinated polyethylene are banburying at 150°C for 15 minutes to obtain a banburying material A; the nitrile rubber and maleic anhydride grafted polypropylene are banburying at 130°C for 10 minutes to obtain a banburying material B; the banburying materials A and B are mixed and banburying at 130°C for 15 minutes to obtain a composite modified rubber.

[0064] Among them, the particle size of polytetrafluoroethylene powder is less than 20 μm. The particle size of magnesium hydroxide is less than 5 μm. The particle size of basalt fiber powder is less than 15 μm. The particle size of ammonium polyphosphate is less than 10 μm. The particle size of zinc borate is less than 5 μm.

[0065] The vulcanizing agent includes bisphenol AF and phenyl-phenyl-diisopropylbenzene peroxide (DCP-S), and the mass ratio is bisphenol AF:phenyl-diisopropylbenzene peroxide (DCP-S) = 6:2.5.

[0066] The accelerator includes accelerator M (2-mercaptobenzothiazole) and accelerator TMTD (tetramethylthiuram disulfide), and the mass ratio is accelerator M (2-mercaptobenzothiazole): accelerator TMTD (tetramethylthiuram disulfide) = 6:2.5.

[0067] The antioxidant is antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer) or antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine).

[0068] Wherein, the plasticizer is dioctyl phthalate.

[0069] The method for preparing the above-mentioned oil-resistant flame-retardant composite sealing material comprises the following steps: S1: premix polytetrafluoroethylene powder, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate and zinc borate uniformly according to weight proportions to obtain a mixture A; S2: Add the composite modified rubber into an internal mixer according to the mass fraction, and mix at 60°C for 5 minutes; then add hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, and E-GMA-VA terpolymer, and mix at 100°C for 5 minutes; then add mixture A, and mix at 120°C for 15 minutes; then add triphenyl phosphate and expandable graphite, and mix at 150°C for 15 minutes; then cool to 90°C, add vulcanizer, accelerator, antioxidant and plasticizer, and mix at 90°C for 15 minutes to obtain a mixed material; S3: performing compression molding on the mixed material, wherein the compression molding temperature is controlled at 160° C. and the compression molding pressure is controlled at 15 MPa to obtain a molding material; S4: Put the molding material into the vulcanization equipment for vulcanization treatment. The vulcanization treatment parameters are: primary vulcanization, temperature 160°C, time 10min, pressure 15MPa; secondary vulcanization, temperature 180°C, time 20min, pressure 20MPa; tertiary vulcanization, temperature 220°C, time 20min, pressure 20MPa; cooling, trimming, and obtaining the sealing material.

[0070] The oil-resistant and flame-retardant composite sealing material of this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.5 mm.

[0071] Example 5: An oil-resistant and flame-retardant composite sealing material, the sealing material comprising the following raw materials in parts by mass: 98 parts of composite modified rubber, 5 parts of polytetrafluoroethylene powder, 1.5 parts of hydrogenated polyisobutylene, 1 part of vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, 3 parts of E-GMA-VA terpolymer, 8 parts of magnesium hydroxide, 10 parts of basalt fiber powder, 1 part of ammonium polyphosphate, 3 parts of triphenyl phosphate, 0.5 part of expandable graphite, 5 parts of zinc borate, 1.5 parts of vulcanizer, 1.5 parts of accelerator, 1 part of antioxidant and 8 parts of plasticizer.

[0072] The preparation method of the composite modified rubber includes the following steps: according to the mass ratio of fluororubber:nitrile rubber:ethylene propylene diene rubber:chlorinated polyethylene:maleic anhydride grafted polypropylene = 50:20:5:5:1, the fluororubber, ethylene propylene diene rubber and chlorinated polyethylene are banburying at 150°C for 10 minutes to obtain a banburying material A; the nitrile rubber and maleic anhydride grafted polypropylene are banburying at 130°C for 5 minutes to obtain a banburying material B; the banburying materials A and B are mixed and banburying at 130°C for 10 minutes to obtain a composite modified rubber.

[0073] Among them, the particle size of polytetrafluoroethylene powder is less than 20 μm. The particle size of magnesium hydroxide is less than 5 μm. The particle size of basalt fiber powder is less than 15 μm. The particle size of ammonium polyphosphate is less than 10 μm. The particle size of zinc borate is less than 5 μm.

[0074] The vulcanizing agent includes bisphenol AF and phenyl-phenyl-diisopropylbenzene peroxide (DCP-S), and the mass ratio is bisphenol AF:phenyl-diisopropylbenzene peroxide (DCP-S) = 6:2.2.

[0075] The accelerator includes accelerator M (2-mercaptobenzothiazole) and accelerator TMTD (tetramethylthiuram disulfide), and the mass ratio is accelerator M (2-mercaptobenzothiazole): accelerator TMTD (tetramethylthiuram disulfide) = 6:2.2.

[0076] The antioxidant is antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer) or antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine).

[0077] Wherein, the plasticizer is dioctyl phthalate.

[0078] The method for preparing the above-mentioned oil-resistant flame-retardant composite sealing material comprises the following steps: S1: premix polytetrafluoroethylene powder, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate and zinc borate uniformly according to weight proportions to obtain a mixture A; S2: Add the composite modified rubber into an internal mixer according to the mass fraction, and mix at 60°C for 3 minutes; then add hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer, and E-GMA-VA terpolymer, and mix at 100°C for 3 minutes; then add mixture A, and mix at 120°C for 10 minutes; then add triphenyl phosphate and expandable graphite, and mix at 150°C for 10 minutes; then cool to 90°C, add vulcanizer, accelerator, antioxidant and plasticizer, and mix at 80°C for 15 minutes to obtain a mixed material; S3: performing compression molding on the mixed material, wherein the compression molding temperature is controlled at 140° C. and the compression molding pressure is controlled at 25 MPa to obtain a molding material; S4: Put the molding material into the vulcanization equipment for vulcanization treatment. The vulcanization treatment parameters are: primary vulcanization, temperature 150°C, time 10min, pressure 10MPa; secondary vulcanization, temperature 180°C, time 15min, pressure 20MPa; tertiary vulcanization, temperature 180°C, time 20min, pressure 15MPa; cooling, trimming, and obtaining the sealing material.

[0079] The oil-resistant and flame-retardant composite sealing material of this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.5 mm.

[0080] In the above embodiments, the cross-linked vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane polymer used is model KNK-HR910, Guangzhou Xiaojia Chemical Technology Co., Ltd. E-GMA-VA terpolymer is model BF-7B, Shenzhen Minjian Plastics Co., Ltd. The particle size of expandable graphite is below 200 mesh sieve, the expansion rate is more than 200 times, model ZX-S, Lingshou County Zhengxu Mineral Products Processing Plant.

[0081] Comparative Example 1 No hydrogenated polyisobutylene is added to the sealing material, that is, no hydrogenated polyisobutylene is added when preparing the composite modified rubber, and the component content of hydrogenated polyisobutylene is replaced by fluororubber; other parameters and methods are the same as in Example 1.

[0082] Comparative Example 2 No maleic anhydride grafted polypropylene is added to the sealing material, that is, no maleic anhydride grafted polypropylene is added when preparing the composite modified rubber, and the component content of the maleic anhydride grafted polypropylene is replaced by fluororubber; other parameters and methods are the same as in Example 1.

[0083] Comparative Example 3 No vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer is added to the sealing material; other parameters and methods are the same as in Example 1.

[0084] Comparative Example 4 No E-GMA-VA terpolymer is added to the sealing material; other parameters and methods are the same as in Example 1.

[0085] Comparative Example 5 No vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer and E-GMA-VA terpolymer are added to the sealing material; other parameters and methods are the same as in Example 1.

[0086] Comparative Example 6 No basalt fiber powder is added to the sealing material; other parameters and methods are the same as in Example 1.

[0087] Comparative Example 7 No expandable graphite is added to the sealing material; other parameters and methods are the same as in Example 1.

[0088] Comparative Example 8 No zinc borate is added to the sealing material; other parameters and methods are the same as in Example 1.

[0089] Comparative Example 9 No basalt fiber powder, expandable graphite and zinc borate are added to the sealing material; other parameters and methods are the same as in Example 1.

[0090] Comparative Example 10 When preparing the composite modified rubber, no nitrile rubber is added, and the content of nitrile rubber is replaced by fluororubber; other parameters and methods are the same as in Example 1.

[0091] Comparative Example 11 When preparing the composite modified rubber, chlorinated polyethylene is not added, and the content of chlorinated polyethylene is replaced by fluororubber; other parameters and methods are the same as in Example 1.

[0092] Comparative Example 12 When preparing the composite modified rubber, no nitrile rubber and chlorinated polyethylene are added at the same time, and the content of nitrile rubber and chlorinated polyethylene is replaced by fluororubber; other parameters and methods are the same as in Example 1.

[0093] Comparative Example 13 Only bisphenol AF (2.2 parts) was used as the vulcanizing agent; other parameters and methods were the same as those in Example 1.

[0094] Comparative Example 14 The vulcanizing agent used was only phenyl-diisopropyl peroxide (2.2 parts); other parameters and methods were the same as in Example 1.

[0095] Comparative Example 15 The accelerator used was only accelerator M (1 part); other parameters and methods were the same as those in Example 1.

[0096] Comparative Example 16 The accelerator used was only accelerator TMTD (1 part); other parameters and methods were the same as in Example 1.

[0097] The performance of the sealing material samples prepared in the above embodiments and comparative examples was tested.

[0098] 1. Using samples of each embodiment and each comparative example respectively, referring to GB / T531.1, GB / T528, GB / T529, GB / T1683, GB / T15256 and other testing specifications, corresponding specimens with different test requirements were prepared, and performance tests were carried out according to the test methods of vulcanized rubber. The results are shown in Table 1 below.

[0099] Table 1 Conventional performance test results

[0100] From the above results, it can be seen that there is no significant difference in hardness, tensile strength at break, elongation at break and tear strength between the embodiments and the comparative examples; from comparative example 1, it can be seen that without adding hydrogenated polyisobutylene, the oil absorption rate at 80°C increases, and the oil resistance of the material weakens; from comparative example 2, it can be seen that without adding maleic anhydride grafted polypropylene to the composite modified rubber, the oil absorption rate at 80°C increases, and the oil resistance of the material weakens; from comparative examples 3 to 4, it can be seen that without adding vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer or E-GMA-VA terpolymer, the oil absorption rate at 80°C increases. The oil resistance of the material is weakened by the increase; from Comparative Example 5, it can be seen that without adding vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer and E-GMA-VA terpolymer at the same time, the oil absorption rate at 80°C is significantly increased, and the oil resistance of the material is greatly weakened; from Comparative Examples 6 to 8, it can be seen that without adding basalt fiber powder, expandable graphite or zinc borate, the oil absorption rate at 80°C increases, and the oil resistance of the material is weakened; from Comparative Example 9, it can be seen that without adding basalt fiber powder, expandable graphite and zinc borate at the same time, the oil absorption rate at 80°C increases significantly, and the oil resistance of the material is greatly weakened. From Comparative Examples 10 and 12, it can be seen that adding nitrile rubber to the composite modified rubber can comprehensively improve the oil resistance of the sealing material. When nitrile rubber and chlorinated polyethylene are not added at the same time, the oil resistance will be reduced. The combination of fluororubber, nitrile rubber and chlorinated polyethylene can well improve the oil resistance of the sealing material. Comparative Example 13 shows that when bisphenol AF vulcanizing agent is used alone, the mechanical properties of the sealing material decrease, and the combination of the two vulcanizing agents can improve the mechanical properties of the sealing material. Comparative Examples 15 and 16 show that when only accelerator M or only accelerator TMTD is used, the tensile strength and tear strength of the sealing material decrease.

[0101] 2. The oil resistance test was carried out on the samples of each embodiment and each comparative example according to the liquid resistance test for vulcanized rubber GB / T1690, using No. 3 standard oil and the test conditions: 120°C×80h; the sealing material was made into a 2mm gasket, installed on a continuous high-temperature oil sealing equipment for trial use, and the service life was tested. Oil leakage means that replacement is required; the results are shown in Table 2 below.

[0102] Table 2 Performance test results after aging or oil immersion

[0103] From the above results, it can be seen that the tensile strength at break measured after the oil resistance test of Examples 1 to 5 is still maintained at more than 15MPa, the elongation at break is maintained at more than 304%, the service life at 120°C can reach more than 200d, and the oil resistance of the material is good; from Comparative Example 1, it can be seen that without adding hydrogenated polyisobutylene, the tensile strength at break, elongation at break and service life measured after the oil resistance test are all reduced, and the oil resistance of the material is weakened; from Comparative Example 2, it can be seen that without adding maleic anhydride grafted polypropylene to the composite modified rubber, the tensile strength at break, elongation at break and service life measured after the oil resistance test are all reduced, and the oil resistance of the material is weakened; from Comparative Examples 3 to 4, it can be seen that without adding vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer or E-GMA-VA terpolymer, the tensile strength at break, elongation at break and service life measured after the oil resistance test are all The oil resistance of the material is weakened; from Comparative Example 5, it can be seen that without adding vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer and E-GMA-VA terpolymer at the same time, the tensile strength at break measured after the oil resistance test is reduced to 10.66MPa, the elongation at break is reduced to 230%, and the service life is reduced to 147d, and the oil resistance of the material is greatly weakened; from Comparative Examples 6 to 8, it can be seen that without adding basalt fiber powder, expandable graphite or zinc borate, the tensile strength at break, elongation at break and service life measured after the oil resistance test are all reduced, and the oil resistance of the material is weakened; from Comparative Example 9, it can be seen that without adding basalt fiber powder, expandable graphite and zinc borate at the same time, the tensile strength at break measured after the oil resistance test is reduced to 9.08MPa, the elongation at break is reduced to 198%, and the service life is reduced to 130d, and the oil resistance of the material is greatly weakened. It can be seen from Comparative Examples 10, 11 and 12 that the combination of fluororubber, nitrile rubber and chlorinated polyethylene can well improve the oil resistance and aging resistance of the sealing material. It can be seen from Comparative Example 14 that the aging resistance of the phenyl-diisopropylbenzene peroxide vulcanizing agent alone decreases, and the combination of the two vulcanizing agents can improve the aging resistance of the sealing material. It can be seen from Comparative Examples 15 and 16 that the aging resistance of the sealing material decreases when only accelerator M or only accelerator TMTD is used, and the combination of the two accelerators can improve the aging resistance and heat resistance of the sealing material.

[0104] 3. Flame retardant performance test The following experiments were conducted using samples of each embodiment and each comparative example: 1. The vertical combustion grade was measured using a vertical combustion instrument according to the UL94-2018 standard, and the sample size was 100 mm × 15 mm × 2 mm. 2. The combustion oxygen index was measured according to the oxygen index method for rubber combustion performance measurement in GB / T10707. The results are shown in Table 3 below.

[0105] Table 3 Flame retardant performance test results

[0106] From the above results, it can be seen that the UL vertical combustion rating of Examples 1 to 5 is FV-0, the oxygen index can reach more than 35.8%, and the flame retardant performance of the material is good; from Comparative Example 1, it can be seen that without adding hydrogenated polyisobutylene, the oxygen index is reduced, indicating that the flame retardant performance of the material is reduced; from Comparative Example 2, it can be seen that without adding maleic anhydride grafted polypropylene to the composite modified rubber, the oxygen index is reduced, indicating that the flame retardant performance of the material is reduced; from Comparative Examples 3 to 4, it can be seen that without adding vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer or E-GMA-VA terpolymer, the oxygen index is reduced, indicating that the flame retardant performance of the material is reduced; As shown in Example 5, without adding vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer and E-GMA-VA terpolymer, the vertical combustion grade is FV-1, and the oxygen index is reduced to 26.0%, indicating that the flame retardancy of the material is significantly reduced; from Comparative Examples 6 to 8, it can be seen that without adding basalt fiber powder, expandable graphite or zinc borate, the vertical combustion grade is FV-1, the oxygen index is reduced, and the oil resistance of the material is weakened; from Comparative Example 9, it can be seen that without adding basalt fiber powder, expandable graphite and zinc borate, the vertical combustion grade is FV-2, and the oxygen index is reduced to 24.4%, indicating that the flame retardancy of the material is significantly reduced. From Comparative Examples 11 and 12, it can be seen that adding chlorinated polyethylene to the composite modified rubber can comprehensively improve the flame retardancy of the sealing material; when nitrile rubber and chlorinated polyethylene are not added at the same time, the flame retardancy will be reduced, and the combination of fluororubber, nitrile rubber and chlorinated polyethylene can well improve the flame retardancy of the sealing material.

Claims

1. An oil-resistant and flame-retardant composite sealing material, characterized in that: The sealing material includes the following raw materials in parts by mass: 72 to 98 parts of composite modified rubber, 5 to 10 parts of polytetrafluoroethylene powder, 0.5 to 1.5 parts of hydrogenated polyisobutylene, 1 to 3 parts of vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane cross-linked polymer, 1 to 3 parts of E-GMA-VA terpolymer, 8 to 12 parts of magnesium hydroxide, 5 to 10 parts of basalt fiber powder, 1 to 3 parts of ammonium polyphosphate, 1 to 3 parts of triphenyl phosphate, 0.5 to 0.8 parts of expandable graphite, 2 to 5 parts of zinc borate, 1.5 to 3 parts of vulcanizer, 0.5 to 1.5 parts of accelerator, 1 to 2 parts of antioxidant and 5 to 8 parts of plasticizer.

2. The oil-resistant and flame-retardant composite sealing material according to claim 1, characterized in that: The preparation method of the composite modified rubber comprises the following steps: in a mass ratio of fluororubber:nitrile rubber:ethylene propylene diene rubber:chlorinated polyethylene:maleic anhydride grafted polypropylene=(50-60):(15-20):(5-10):(1-5):(1-3), the fluororubber, ethylene propylene diene rubber and chlorinated polyethylene are banburying at 130-150°C for 10-15 minutes to obtain a banburying material A; the nitrile rubber and maleic anhydride grafted polypropylene are banburying at 110-130°C for 5-10 minutes to obtain a banburying material B; the banburying materials A and B are mixed and banburying at 110-130°C for 10-15 minutes to obtain a composite modified rubber.

3. The oil-resistant and flame-retardant composite sealing material according to claim 1, characterized in that: The particle size of the polytetrafluoroethylene powder is less than 20 μm; the particle size of the magnesium hydroxide is less than 5 μm; the particle size of the basalt fiber powder is less than 15 μm; the particle size of the ammonium polyphosphate is less than 10 μm; and the particle size of the zinc borate is less than 5 μm.

4. The oil-resistant and flame-retardant composite sealing material according to claim 1, characterized in that: The vulcanizing agent includes bisphenol AF and phenyl-diisopropylbenzene peroxide, and the mass ratio is bisphenol AF:phenyl-diisopropylbenzene peroxide = (5-6): (2-3).

5. The oil-resistant and flame-retardant composite sealing material according to claim 1, characterized in that: The accelerator includes accelerator M and accelerator TMTD, and the mass ratio of accelerator M: accelerator TMTD is (5-6): (2-3).

6. The oil-resistant and flame-retardant composite sealing material according to claim 1, characterized in that: The antioxidant is antioxidant RD or antioxidant 4010NA.

7. The oil-resistant and flame-retardant composite sealing material according to claim 1, characterized in that: The plasticizer is dioctyl phthalate.

8. A method for preparing an oil-resistant flame-retardant composite sealing material, used for preparing the oil-resistant flame-retardant composite sealing material according to claim 1, characterized in that: The preparation method comprises the following steps: S1: premix polytetrafluoroethylene powder, magnesium hydroxide, basalt fiber powder, ammonium polyphosphate and zinc borate uniformly according to weight proportions to obtain a mixture A; S2: Add the composite modified rubber into an internal mixer according to the mass fraction, and mix at 40℃~60℃ for 3min~5min; then add hydrogenated polyisobutylene, vinyl polydimethylsiloxane-polymethylsiloxane silsesquioxane crosslinked polymer, and E-GMA-VA terpolymer, and mix at 80℃~100℃ for 3min~5min; then add mixture A, and mix at 100℃~120℃ for 10min~15min; then add triphenyl phosphate and expandable graphite, and mix at 130℃~150℃ for 10min~15min; then cool to 80℃~90℃, add vulcanizer, accelerator, antioxidant and plasticizer, and mix at 80℃~90℃ for 10min~15min to obtain a mixed material; S3: Extruding or compression molding the mixed material to obtain a molding material; S4: placing the molding material into a vulcanization device for vulcanization treatment to obtain a sealing material.

9. The method for preparing an oil-resistant and flame-retardant composite sealing material according to claim 8, characterized in that: In S3, the temperature of the extrusion molding is controlled at 60°C to 80°C, the temperature of the compression molding is controlled at 140°C to 160°C, and the pressure of the compression molding is controlled at 15MPa to 25MPa.

10. The method for preparing an oil-resistant and flame-retardant composite sealing material according to claim 8, characterized in that: In S4, the parameters of the vulcanization treatment are: primary vulcanization, temperature 150°C ~ 160°C, time 5min ~ 10min, pressure 10MPa ~ 15MPa; secondary vulcanization, temperature 160°C ~ 180°C, time 15min ~ 20min, pressure 15MPa ~ 20MPa; tertiary vulcanization, temperature 180°C ~ 220°C, time 15min ~ 20min, pressure 15MPa ~ 20MPa.

Citation Information

Patent Citations

  • Novel-engine-oil-resistant sealing material and preparation method thereof

    CN104672727A

  • Flame-retardant sealing ring for motors of range hoods

    CN106317514A

  • Oil-resistant flame-retardant ozone-resistant rubber and preparation method thereof

    CN108485013A

  • Oil-resistant and heat-resistant sealing material as well as preparation method and application thereof

    CN118344739A

Cited By

  • A foam tape based on EPDM rubber

    CN119752055A

  • Medium-resistant high-elasticity rubber material for sealing element and preparation method of medium-resistant high-elasticity rubber material

    CN120623724A

  • Flexible carbonized flame-retardant thermal insulation material as well as preparation method and application thereof

    CN120795400A

  • Flexible carbonized flame-retardant thermal insulation material and preparation method and application thereof

    CN120795400B

  • High-temperature-resistant rubber sealing ring and preparation method thereof

    CN121427221A